Influence of gold nanorods on the structure and photonic bandgap in a twist grain boundary phase with smectic C* blocks - Sahoo, Rajalaxmi; Rao, D. S. Shankar; Hiremath, Uma S.; Yelamaggad, V. C.; Shinde, Pravin; Bhagavatula L. V. Prasad; Prasad, S. Krishna (Journal of Molecular Liquids, 2020)
We describe the first report of the influence of gold nanorods (GNR) on the induced twist grain boundary smectic C* (TGBC*) phase in a binary mixture of achiral bent-core and chiral linear liquid crystals. The GNR concentration-dependent phase diagram of these nanocomposites shows that the thermal range of this twist grain boundary phase having smectic C* blocks phase increases by 50% for an intermediate composition compared to that for the host binary mixture without nanorods. The inclusion of the nanorods is seen to have substantial effect on the structural and photonic bandgap features of the TGBC* phase. For example, the helical periodidty gets altered in all the three dimensions: while those within the block undergo a huge increase, the one which is orthogonal to the blocks, shrinks. The spacing of the square grid pattern arising normal to the TGB helix direction increases for the nanocomposites getting even doubled for a certain composition, a feature evidenced by optical microscopy as well as optical diffraction. Xray diffraction clearly brings out the feature that the presence of GNR alters the thermal character of the transition between the TGBC* and the cholesteric phase. Quantitative analysis of the data indicates that the system would remain in the vicinity of a possible tricritical point, a behavior having wider ramifications to understand the underlying critical phenomenon. Based on the experimental observations, and capturing the essence of the reported adaptive defect core targeting mechanism we propose a model wherein GNRs get confined in the grain boundary region. This feature offers a potential to have periodic and anisotropic plasmonic structure arising out of the synergetic interactions between the metal nanorod and the twisted grain boundary structure. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: 3D photonic bandgap; Gold nanorods; Induced phase; TGBC* phase; Tricritical phenomena